Suicidality in Patients With Epilepsy: Why Should Neurologists Care? - Kanner, Andres M. (Frontiers in Integrative Neuroscience, 2022)
Suicidality is a relatively common comorbidity in patients with epilepsy (PWE). Population-based studies have revealed lifetime prevalence rates of 25% of suicidal ideation. In addition, PWE without comorbid psychiatric disorders have a two to three higher risk of committing suicide and this risk increases by 12 to 32-fold in the presence of various psychiatric disorders. Risk factors are multiple and include socio-demographic, genetic, age and gender and psychiatric comorbidities. Among the latter, mood, anxiety and psychotic disorders have been found to be common risk factors for suicidality in PWE, but iatrogenic causes resulting from pharmacotherapy with antiseizure drugs or epilepsy surgery can also cause suicidal ideation and behavior. Suicidality and epilepsy have a complex bidirectional relation, where PWE are at increased risk of suicidality and vice-versa. Common pathogenic mechanisms operant in both conditions may explain this bidirectional relation. Suicidal ideation can be easily identified in outpatient epilepsy clinics with screening instruments which can be treated and thus prevent its escalation to suicidal attempts and completed suicide. The aim of this article is to review these data in detail.